Feasibility, acceptability, and bacterial recovery for community-based sample collection to estimate antibiotic resistance in commensal gut and upper respiratory tract bacteria - Tran, HH; Nguyen, HAT; Tran, HB; Vu, BNT; Nguyen, TCT; Tacoli, C; Tran, TP; Trinh, TS; Cai, THN; Nadjm, B; Tran, KHT; Pham, QD; et al. (Springer Nature, 2022)
Vietnam has high rates of antibiotic use and resistance. Measuring resistance in commensal bacteria could provide an objective indicator for evaluating the impact of interventions to reduce antibiotic use and resistance. This study aimed to evaluate the feasibility, acceptability, and bacterial recovery for different sampling strategies. We conducted a cross-sectional mixed methods study in a rural community in Ha Nam Province, northern Vietnam, and collected structured interviews, samples, and in-depth interviews from households. Out of 389 households invited, 324 participated (83%), representing 1502 individuals. Samples were collected from these individuals (1498 stool, 1002 self-administered nasal swabs, and 496 HW-administered nasopharyngeal swabs). Pneumococci were recovered from 11.1% (128/1149) of the total population and 26.2% (48/183) of those under 5-years. Recovery was higher for health-worker (HW)-administered swabs (13.7%, 48/350) than self-administered swabs (10.0%, 80/799) (OR 2.06, 95% CI 1.07–3.96). Cost per swab was cheaper for self-administered (USD 7.26) than HW-administered (USD 8.63) swabs, but the overall cost for 100 positive samples was higher (USD 7260 and USD 6300 respectively).﻿ Qualitative interviews revealed that HW-administered nasopharyngeal swabs took longer to collect, caused more discomfort, and were more difficult to take from children. Factors affecting participation included sense of contribution, perceived trade-offs between benefits and effort, and peer influence. Reluctance was related to stool sampling and negative perceptions of research. This study provides important evidence for planning community-based carriage studies, including cost, logistics, and acceptability. Self-administered swabs had lower recovery, and though cheaper and quicker, this would translate to higher costs for large population-based studies. Recovery might be improved by swab-type, transport medium, and better cold-chain to lab.